Methods of loading balancing for Web-servers - Жуков, І. А.; Кравець I. М. (Problems of Informatization and Control, 2007)
The most widespread methods of loading balancing for the increase of fast-acting, productivity and providing continuous work of Web-servers are considered. Each of methods was investigated relatively to: balancing, fault tolerance and administration. The mixed schemes of loading balancing for Web-servers are also examined